The Bachelor of Physical Education graduates of the College of PESCAR, WVSU an evaluation - Gregorios, Eva Rose R. (2002)
This follow-up study of the graduate of the College of PESCAR determined the following:(1) the satisfaction of the respondents with their undergraduate preparation in areas of their specialization (teaching PE, coaching, officiating, and sports management) (2) relevance of the major courses in the BPE curriculum to respondents employed as PE teachers, coaches,and sports officials. (3) skills that respondents believe were needed by Physical Education teachers and teacher-coaches in the field nowadays. One hundred three (103) BPE graduates of the College from batches 1994 to 2000 accomplished a validated questionnaire to obtain data on their personal profile, preparation evaluation, course evaluation, and skill suggestions. Data analyses of the preparation evaluation showed that the respondents, in general, were very satisfied with their undergraduate preparation at the College of PESCAR. They felt that they had a very good preparation in all four areas of their specialization. The level of their satisfaction was further analyzed through the Kolmogorov-Smirnov test to examine differences when they were grouped according to curriculum finished and teaching experience. Result showed that respondents' level of satisfaction did not significantly differ when they were grouped according to gender, employability, employment status, and teaching experience. However, when they were grouped according to the curriculum they finished, the respondents who finished the 2nd revised curriculum revealed significantly higher satisfaction than the original and 1st revised groups, and the respondents who finished the 1st revised curriculum revealed significantly lower satisfaction than the other two groups.The analyses of the course evaluation of respondents employed as PE teachers, coaches, and sports officials revealed that 80% of the courses in the original curriculum were very relevant and 20% were relevant. Sixty-five percent (65%) of the courses in the 1st revised curriculum were very relevant, 26% were relevant,and 9% were not relevant. Eighty-four percent (84%) of the courses in the 2nd revised curriculum were very relevant and 16% were relevant. When the respondents were asked if there were courses that they wanted to remove from their curriculum, 98.1% answered "no" to the question and 1.9% answered "yes". The courses that the respondents who answered "yes" wanted to remove were ballet and badminton II.. The general evaluation of these courses indicated that both were "very relevant"; however, 2 of the respondents disagreed to this result.When respondents were asked if there were courses that they wanted to add to their curriculum these courses: rowing, canoeing, arnis, scouting, dance composition, research in sports, 2nd level sport courses (coaching and officiating), and tae kwon do. The respondents believed that the following skills were needed by PE teachers and teacher-coaches in the field nowadays: (a) In sports: fundamental skills in different sports, physical fitness, cognitive skills, coaching, officiating, and team management skills. (b) In Dance: fundamental skills in different dances, aesthetic skills, physical fitness, and rhythmic skills. (c) In Teaching: professional skills, specifically mastery of the subject matter, classroom management and motivation, and personal skills as sense of humor, objectivity and industry. (d) Others : research and communication (both oral and written )skills.